Providing evidence for a well-worn stereotype: Italians and Swedes do gesture differently - Graziano, Maria; Gullberg, Marianne (Frontiers in Communication, 2024)
Across cultures and languages spontaneous speech is often accompanied by gestures. It is a popular belief that people in Italy gesture more than people in Northern Europe, such as in Sweden. Despite this general assumption few studies empirically investigate cultural differences in gesture frequency and gesture function under similar circumstances. This study compares the spoken and gestural behaviours of Italian and Swedish speakers, assumed to represent gesture-rich vs. gesture-sparse cultures. We examine the groups' gestural behaviour for frequency, and in terms of possible differences in rhetorical style probing the distribution of gestural functions (referential vs. pragmatic; Kendon, 2004a) across narrative levels (narrative, metanarrative, and paranarrative;McNeill, 1992). The results show that 1) Italians overall do gesture more than Swedes; 2) Italians produce more pragmatic gestures than Swedes who produce more referential gestures; 3) both groups show sensitivity to narrative level: referential gestures mainly occur with narrative clauses, and pragmatic gestures with meta-and paranarrative clauses. However, the overall group preferences for different functions still lead to different styles. These findings indicate that the two groups differ in gesture rate and, more interestingly, in rhetorical styles, one focused on events and actions in speech and gesture (Swedish), the other alternating between events in speech and gesture, and the highlighting of the presentation of new pieces of information in gesture only (Italian). We propose that the findings suggest that the two groups conceptualise narrative production in different ways reflected in two different rhetorical styles revealed by gesture production more than by speech.